The Development of Flora and Fauna Conservation Area Through Signage and Digital Map: Study on Srengseng Urban Forest, West Jakarta - Lim, Handy; Cahyani, Fathiya Agmariyan; Amelia, Anak Agung Dhea; Angelica, Melva; Ayu, Jati Paras (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2024)
This research aims to identify and analyze the development of flora and fauna conservation areas through signage and digital maps in Srengseng Urban Forest, West Jakarta. The research method used is a qualitative method described by descriptive analysis conducted through in-depth interviews and documentation. This research concludes that Srengseng Urban Forest has proven unable to develop thoroughly in terms of signposting facilities. The obstacles, such as the lack of directions and the absence of a map of the location, affect the comfort of visitors and safety and hygiene issues. Suggestions that can be given to improve the development of conservation areas in Srengseng Urban Forest are that Srengseng Urban Forest should have multifunctional signage, such as directional signs that include several directions from facilities and attractions in the urban forest with signage placement in strategic locations, such as at the roundabout around the main entrance of the Srengseng Urban Forest. In addition to creating multifunctional signage, Srengseng Urban Forest also needs to have a digital map type map that visitors can access by scanning a QR Code to show an overall picture of the Srengseng Urban Forest area.